The carbon budget and greenhouse gas balance of annual and perennial crops for dairy feed - Sulaiman, Muhammad Firdaus; Wagner-Riddle, Claudia; Brown, Shannon E.; Warland, Jon; Voroney, Paul; Rochette, Philippe (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Dairy production emits significant amount of greenhouse gases (GHG) to the atmosphere. Nevertheless, cultivation of hay and corn for dairy feed have the potential to partially mitigate GHG emission from dairy production by sequestering carbon in soil as soil organic matter. The present study investigated the net ecosystem carbon budget (NECB) and greenhouse gas balance (GHGB) of a hay and corn field grown side-by-side over three years in Elora, Ontario, Canada, as an indicator of net sequestered carbon. The NECB of the two crops were determined using measurements of net ecosystem exchange (NEE) and carbon in plant and applied manure. The greenhouse gas balance (GHGB) were determined using the NECB plus the total nitrous oxide (N2O) fluxes. On average over the three study years, NECB of hay (7 ± 51 g C m−2 yr−1) was significantly lower than corn (154 ± 79 g C m−2 yr−1) indicating that corn was a larger carbon source than hay. The three-year average GHGB of 796 and 127 g CO2-eq m−2 yr−1 for corn and hay, respectively, indicated that corn was a larger emitter of GHG than hay. The NECB was the more dominant factor than N2O emissions in influencing the outcome of the annual GHGB. In conclusion, hay has a larger potential than corn in sequestering carbon and mitigating GHG emission.